Optimal dose and type of exercise to improve cognitive function in patients with mild cognitive impairment: a systematic review and network meta-analysis of RCTs - Yu, Yingying; Wang, Junjie; Xu, Jian (Frontiers in Psychiatry, 2024)
Background Mild cognitive impairment (MCI) represents a prodromal stage of dementia, characterized by cognitive decline exceeding that expected with normal aging. Exercise interventions have emerged as a promising approach to counter functional decline and enhance cognitive function in the elderly MCI population. However, the optimal exercise modalities and dosage (dose-response relationship) are understudied. Objective It aims to determine the most effective exercise modality for MCI patients by optimizing the dose-response relationship to ensure sufficient intensity to induce positive neurological adaptations. Methods A systematic search of electronic databases, including PubMed, Embase, Scopus, Web of Science, and Cochrane Central Register of Controlled Trials was conducted from inception to April 15, 2024. Studies evaluating the efficacy of exercise interventions in MCI participants were included. Primary outcomes of interest are global cognition and executive function. Random-effects models will be utilized for both pairwise and network meta-analysis. Results Following the application of specific inclusion and exclusion criteria, a total of 42 articles, encompassing 2832 participants, were chosen for inclusion in a network meta-analysis. The findings revealed that multi-component exercise demonstrated superior efficacy in mitigating the deterioration of global cognition, as evidenced by standard mean differences (SMDs) of 1.09 (95% CI: 0.68 to 1.51) compared to passive controls. Additionally, multi-component exercise exhibited a significant impact on executive function, with SMDs of 2.50 (95% CI: 0.88 to 4.12) when contrasted with passive controls. Our research has demonstrated that sessions lasting 30 minutes, occurring 3-4 times per week, with interventions lasting 12-24 weeks and an intensity of 60-85% of maximum heart rate, yield higher effect sizes in improving global cognition. However, sessions lasting 30-61 minutes, with interventions lasting 25 weeks or longer, show greater effectiveness in enhancing executive function. Conclusion A network meta-analysis identified multi-component exercise as the most effective intervention for improving global cognitive and executive function in patients with mild cognitive impairment. Notably, moderate-intensity exercise performed at least three times weekly appears beneficial, with evidence suggesting shorter sessions and higher frequencies may optimize cognitive outcomes.